Urban issues and solutions in the context of sustainable development: A review of the literature - Jurijs Grizans (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2009)
Cities are at the heart of Europe. As four of every five European citizens live in urban areas, their quality of life and the quality of their environment depends upon how cities look and how they function. Cities are also places where business is done, investments are made and jobs are created. In Northern Europe, people spend over 90% of their time inside and in the winter months, this can rise to almost 100%. If they are not inside, people are usually travelling from one building to another, using civil infrastructure facilities such as roads, bridges and railways. For most people in the developed world, most of the time, the urban environment is their environment. As cities continue to grow, increasing attention must be given to the quality of their urban environment and to their livability. Improving the urban environment - and city dweller's quality of life - has become a major issue in the global effort to achieve sustainable development. This literature study focuses on the urban environment issues and solutions in the context of sustainable development. The purpose of this paper is to study the causes and processes of the emergence, formation and development of the city and the urban environment. The field of urban environment comprises a vital area for the application of sustainable development principles, not least because of the scope for conflicts between interpretations of development. As an activity that has clear economic, social and environmental dimensions, urban policy holds considerable potential to make a positive contribution to the practical realization of sustainable development. Urban environment in this paper is seen as a complex social, economic and biophysical system produced by the interaction between a man-made fabric and the physical characteristics of the landscapes.
Keywords: 330; sustainable development; urbanization; city; urban environment; city's metabolism; ecological footprint of city; Stadt; Urbanisierung; Nachhaltige Stadtentwicklung; Nachhaltige Entwicklung; Umweltbelastung; Bibliometrie